History of Arabic literature (Arabic) - Ahmad H.Osman, Rahmah; Ahmad, Muhammad Anwar (Perbadanan Kota Buku, 2021)
This book presents a brief study of the different historical stages of Arabic literature. It is designed for non-native students specializing in Arabic Language and Literature at the Dept. of Arabic Language and Literature at IIUM. It introduces students to the political, social and cultural introductions of Arabic literature and the role of literature in the civilized construction of a nation. It begins with the pre-Islamic era and ends with the modern era. It summarizes the most momentous historical events in each era, the relationship of literature to political events, and the role of literature in society. It sheds light on some important literary issues, notwithstanding the interest in prominent Arabic poetic arts and the different genres in Arabic literary works, juxtaposition the literati and legendary poets in each era.